2017
DOI: 10.1002/cjce.22745
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of scale‐up dimensionless groups methodology of gas‐solid fluidized beds using advanced non‐invasive measurement techniques (CT and RPT)

Abstract: The most common scale‐up methodology for gas‐solid fluidized bed reactors that has been reported in the literature is based on matching the dimensionless groups. This scale‐up methodology in the literature has been validated by only measuring global hydrodynamic parameters (overall holdups and pressure drop, etc.) without details. Therefore, in this work, we have applied advanced non‐invasive measurement techniques, gamma‐ray computed tomography (CT) and radioactive particle tracking (RPT) techniques, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 25 publications
(68 reference statements)
0
27
0
Order By: Relevance
“…Particle size distribution (PSD), thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR) are prominent in the cluster. [16][17][18][19] The other techniques mostly relate to particle characterization (AAS, EDX, DSC, UPS). [20][21][22][23] The red cluster to the left is remote from the blue and green clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Particle size distribution (PSD), thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR) are prominent in the cluster. [16][17][18][19] The other techniques mostly relate to particle characterization (AAS, EDX, DSC, UPS). [20][21][22][23] The red cluster to the left is remote from the blue and green clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum fluidization velocity (U mf ) was measured from the profiles of pressure drop versus gas velocity (U g ) and the results were compared with the predictions of the empirical correlation available in the literature. [22] It was found that the comparison of the values is in good agreement (see Efhaima and Al-Dahhan [23] ). The values were 10 cm/s and 12 cm/s for the 44 cm and 14 cm columns respectively.…”
Section: Methodsmentioning
confidence: 66%
“…The superficial gas velocities used were 1.5–3 Umf, where the Umf is the minimum fluidization velocity. These gas velocities covered the bubbling and turbulent flow regime based on the previous work performed in our laboratory . The static bed height above the distributor was kept constant at H/D = 2 for the two columns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eng. published 22 articles on fluidized beds and the top 3 concentrated on modelling: hydrodynamics of slot‐rectangular spouted beds; sorption enhanced steam methane reforming in binary fluidized beds; and scale‐up dimensionless groups derived from non‐invasive measurements . The three articles in Can.…”
Section: Applicationsmentioning
confidence: 99%